Death, power, and Queenship: funeral portraits for Queen Margaret of Austria in Italy - Yelsy Hernández Zamora (Los Libros de la Corte.es)
In 1611, Queen Margaret of Austria of Spain died at the age of twenty-six after giving birth to her eighth child. This event triggered a series of customary rituals, funeral orations, and publications in homage to the queen throughout the Iberian world, threading narratives about the queen’s life that highlighted her virtuous behavior and religious piety. This article focuses on the books of funeral ceremonies produced in Italy, specifically in Naples and Florence, which offered an idealized vision of the deceased monarch to endure in the collective memory. The relationship between texts, emblems, and engravings contained in the books outline a posthumous portrait of the queen as a model of queenship worthy of imitation by attributing specific functions and virtues to the female ruler while revealing the political use of Margaret as a symbol connecting the Spanish Crown with the Italian territories.